ANALISIS PENGARUH PENGELUARAN PEMERINTAH TERHADAP STUNTING - Destianti, Anisha; Aji Suseno, Deky (Penerbit Lafadz Jaya, 2025)
Reducing stunting rates is one of the national development priorities outlined in the 2020–2024 National Medium-Term Development Plan (RPJMN) as part of efforts to develop high-quality human resources. This study aims to analyze the effect of government spending on stunting prevalence across 34 provinces in Indonesia during the 2021–2023 period. The independent variables analyzed include the Physical Special Allocation Fund for Stunting (DAK Fisik Stunting), the Non-Physical Special Allocation Fund for Stunting (DAK Non Fisik Stunting), and Village Funds. The intervening variables consist of access to proper sanitation and access to basic health facilities (AFKD), while the dependent variable is stunting prevalence. The method used is Partial Least Squares Structural Equation Modeling (PLS-SEM), with the aid of the WarpPLS 8.0 software. The results show that the Physical DAK for Stunting has a significant negative effect on sanitation (β = -0.46; p < 0.01) and indirectly reduces stunting prevalence. The Non-Physical DAK has a positive effect on sanitation (β = 0.17; p < 0.04) and a direct negative effect on stunting (β = -0.31; p < 0.01). Village Funds significantly affect AFKD (β = -0.53; p < 0.01), which in turn has a significant impact on reducing stunting (β = -0.21; p < 0.02). This model is able to explain 69% of the variation in stunting prevalence (R² = 0.69). These findings provide important implications for results-based budgeting policies aimed at accelerating stunting reduction efforts.